First record of parasitoidism in Danaus erippus (Cramer, 1775) pupae (Lepidoptera, Nymphalidae): A possible mediation by an exotic plant species - Verza, Wenrique; Tavares, Marcelo T.; Eriksson, Alan (Entomological Communications, 2024)
Monarch butterflies have a close relationship with plants of the Apocynaceae family, especially with the genus Asclepias Linnaeus, 1753, using their toxic cardenolides as a defense against predators. Calotropis procera (Aiton) W.T. Aiton, 1811, native from Africa and Asia and introduced in Brazil as an ornamental plant, is a food alternative for monarchs but contains fewer cardenolides than Asclepias, which may make the butterflies more vulnerable to parasitoids. The interaction between wasps of the genus Brachymeria Westwood, 1829 and butterflies of the genus Danaus Kluk, 1802 is seldom reported. This study reports the first case of parasitism by Brachymeria pandora (Crawford, 1914) in pupae of Danaus erippus (Cramer, 1775) in Brazil, collected in the city of Cuiabá, Mato Grosso. Five butterfly pupae were collected on C. procera; three were parasitized, with 34 emergences of parasitoids. We suggest that the relationship between D. erippus and B. pandora may be facilitated by the lower toxicity of C. procera compared to Asclepias, possibly increasing susceptibility to parasitoidism. The high rate of parasitoidism observed suggests that this possible new interaction could be detrimental to the conservation of D. erippus. Further studies are needed to confirm whether this parasitoid-host interaction also occurs with native Asclepias plants and to investigate the impacts of exotic plants on these types of interactions and on butterfly conservation.